PDE4B Induces Epithelial-to-Mesenchymal Transition in Bladder Cancer Cells and Is Transcriptionally Suppressed by CBX7 - Huang, Zhengnan; Liu, Jiakuan; Yang, Jiale; Yan, Yilin; Yang, Chenkai; He, Xiao; Huang, Ruimin; Tan, Mingyue; Wu, Denglong; Yan, Jun; Shen, Bing (Frontiers in Cell and Developmental Biology, 2021)
Urinary bladder cancer (UBC) is a common malignant tumor with high incidence. Advances in the diagnosis and treatment of this disease demand the identification of novel therapeutic targets. Multiple studies demonstrated that PDE4B level was upregulated in malignancies and high PDE4B expression was correlated with poor outcomes. Herein, we identified that PDE4B was a potential therapeutic target in UBC. We confirmed that PDE4B expression was correlated with aggressive clinicopathological characteristics and unfavorable prognosis. Functional studies demonstrated that ectopic expression of PDE4B promoted UBC cells proliferation, migration and invasion, whereas PDE4B depletion suppressed cancer cell aggressiveness. We also identified CBX7 as a regulator of PDE4B to suppress the expression of PDE4B at the transcription level in a PRC1-dependent manner. Moreover, our results indicated that PDE4B induced epithelial-to-mesenchymal transition (EMT) in UBC cells via β-catenin pathway, whereas inhibition of PDE4B by its small molecule inhibitor, rolipram, effectively reversed the PDE4B overexpression-induced effects. To sum up, our results indicated that PDE4B acts as an oncogene by promoting UBC cell migration and invasion via β-catenin/EMT pathway.